Evaluation of Fourier transform infrared spectroscopy and multispectral imaging as means of estimating the microbiological spoilage of farmed sea bream. (June 2019) - Fengou, Lemonia-Christina; Lianou, Alexandra; Tsakanikas, Panagiotis; Gkana, Eleni N.; Panagou, Efstathios Z.; Nychas, George-John E.
Abstract: The objective of the present study was the evaluation of Fourier transform infrared (FTIR) spectroscopy and multispectral imaging (MSI), in tandem with multivariate data analysis, as means of estimating the microbiological quality of sea bream. Farmed whole ungutted fish were stored aerobically at 0, 4 and 8 °C. At regular time intervals, fish samples (i.e. cut portions) were analysed microbiologically, while FTIR and MSI measurements also were acquired at both the skin and flesh sides of the samples. Partial least squares regression (PLSR) models were calibrated to provide quantitative estimations of the microbiological status of fish based on spectral data, in a temperature-independent manner. The PLSR model based on the FTIR data of fish skin exhibited good performance when externally validated, with the coefficient of determination (R 2 ) and the root mean square error (RMSE) being 0.727 and 0.717, respectively. Hence, FTIR spectroscopy appears to be promising for the rapid and non-invasive monitoring of the microbiological spoilage of whole sea bream. Contrarily, the MSI models' performance was unsatisfactory, delimitating their potential exploitation in whole fish quality assessment. Model optimization results concerning fish flesh indicated that MSI may be propitious in skinned fish products, with its definite competence warranting further investigation. Highlights: FTIR spectroscopy and MSI as means of estimating fish microbiological quality. Whole farmed gilthead sea bream was stored aerobically at different temperatures. Partial least squares regression (PLSR) models were calibrated and externally tested. PLSR models based on FTIR fingerprints of fish skin exhibited a good performance. MSI should be further investigated for its application in assessing fish spoilage.